Backfat Thickness Does Affect the Restoration of Ovarian Activity Postpartum in Different Breeding Programs in Zebu Cattle - Martínez, José F.; Galina, Carlos S.; Ortiz, Pablo; Corro, Manuel D.; Rubio, Ivette; Romero-Zuñiga, Juan J. (Frontiers in Veterinary Science, 2021)
The backfat thickness (BFT) was used to forecast the onset of ovarian activity and predict the calf growth. Eighty Brahman cows with their calves were allocated in two groups of 40 distributed in four months according to the month of calving, starting in March and finishing in June. One was synchronized and inseminated at fixed time following by natural mating (TAI+NM); whilst the other only by natural mating (NM). The programs started at 60 ± 5 days postpartum and ended 60 days later. From day 30 postpartum, serial ultrasound examinations and progesterone samples were used to monitor the onset of ovarian activity. The BFT in the rump area was measured by ultrasound from 30 days postpartum and every 15 days thereafter. The weight of the calves was recorded at birth and at weaning on 160 days. The adjusted effect of BFT on ovarian activity and the calves’ development was assessed by binomial logistic regression at 30, 60, 75, and 120 days postpartum. The cycling cows averaged higher BFT irrespective of breeding program (P < 0.001). Also, slower changes in BFT were recorded during the follow-up at each time for all cows. However, the former had the higher BFT values from calving to the end of the study (P < 0.001). At 60, 75, and 120 days, the BFT measured, at the preceding time, was the only factor predicting the commencement of cyclicity (P < 0.001). The accumulative pregnancy through time was higher in TAI+NM (P = 0.003). Daily weight gain and weaning weight of the calves born in March was significantly heavier (P < 0.001) than peers born in April, May, or June. The most critical element to forecast the onset of ovarian activity is the monitoring of BFT around calving regardless of the breeding program. BFT to estimate the development of the calves until weaning was unpredictable.